2021
DOI: 10.1111/ijcp.14987
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of hydrocortisone sodium phosphate penetration into the human aqueous humor after topical application

Abstract: Aim of the study Hydrocortisone is a soft steroid with low anti‐inflammatory properties and a short duration of action, used to manage several ocular conditions. The clinical benefits and side effects associated with hydrocortisone are well documented, but its basic pharmacokinetic in the eye is yet to be fully elucidated. The purpose of this study is to investigate the anterior chamber penetration capabilities of hydrocortisone when used in different concentrations as eye drops treatment. Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Regarding product safety, the use of low-dose hydrocortisone has been shown to be safe in a rabbit model, in which the drug was unable to penetrate the corneal epithelium and was undetectable in the aqueous humor [23]. This was also confirmed by a clinical pharmacokinetics study showing that in patients treated with low-dose hydrocortisone, its concentration remained essentially stable during the study period and was not significantly different from the endogenous cortisol levels normally found in the aqueous humor [27].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Regarding product safety, the use of low-dose hydrocortisone has been shown to be safe in a rabbit model, in which the drug was unable to penetrate the corneal epithelium and was undetectable in the aqueous humor [23]. This was also confirmed by a clinical pharmacokinetics study showing that in patients treated with low-dose hydrocortisone, its concentration remained essentially stable during the study period and was not significantly different from the endogenous cortisol levels normally found in the aqueous humor [27].…”
Section: Discussionmentioning
confidence: 76%
“…A recent randomized clinical trial investigating the pharmacokinetics of hydrocortisone confirmed these findings and demonstrated that the concentration of hydrocortisone in eye drops significantly affects penetration into the anterior chamber of the eye. Specifically, a high concentration of hydrocortisone (0.3%) results in high penetration, whereas a low concentration (0.001%) does not alter the anterior chamber concentration of cortisol, making it a safe option for longer-term treatment [27]. While several studies have explored the therapeutic effects of hyaluronic acid or hydrocortisone separately in the management of DED, the novelty of this research lies in the investigation of a unique combination of 0.2% hyaluronic acid and 0.001% hydrocortisone.…”
Section: Introductionmentioning
confidence: 99%
“…MRA prevents activation of MR pathway by its ligands but it might not activate the GR pathway. Topical dexamethasone sodium phosphate or hydrocortisone sodium phosphate (0.33%) can activate the GR as it does penetrate inside the aqueous humor and the ocular tissues and allows an increase in cortisol endogenous levels in normal individuals 65 67 . Moreover, we showed that in experimental uveitis, only very low dose of intraocular dexamethasone (100 nM) restored the normal glucocorticoid receptor expression, that was down-regulated by LPS injection 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The comparator compound used in the other arm for this study was tailored on another tear substitute containing low dose corticosteroid and registered as a medical device, both containing a similar concentration of sodium hyaluronate. It has been hypothesized that the comparator compound might help to prevent the risk of any recurrence of inflammatory events thanks to the ancillary action of the corticosteroid agent with a low dosage, mild anti-inflammatory and short duration of action [ 27 , 28 , 29 ]. Data available in the previous literature are not comparable to our results, either for different DED models used [ 28 ] or for analytes evaluated [ 27 , 29 ], but taken as a whole would demonstrate an anti-inflammatory effect in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that the comparator compound might help to prevent the risk of any recurrence of inflammatory events thanks to the ancillary action of the corticosteroid agent with a low dosage, mild anti-inflammatory and short duration of action [ 27 , 28 , 29 ]. Data available in the previous literature are not comparable to our results, either for different DED models used [ 28 ] or for analytes evaluated [ 27 , 29 ], but taken as a whole would demonstrate an anti-inflammatory effect in the short term.…”
Section: Discussionmentioning
confidence: 99%